Life in the Big City: Building a Culture of Health - Lumpkin, John (J Public Health Manag Pract, 2015)
This commentary describes Culture of Health, which is the RWJF vision of a shared expectation of the value of health, of individuals and organizations with the capacity to promote widespread well-being, and of healthy lifestyles and access to high-quality health care for everyone.